2010
DOI: 10.1038/nrc2947
|View full text |Cite
|
Sign up to set email alerts
|

Rational, biologically based treatment of EGFR-mutant non-small-cell lung cancer

Abstract: Epidermal growth factor receptor (EGFR)-mutant non-small-cell lung cancer (NSCLC) was first recognized in 2004 as a distinct, clinically relevant molecular subset of lung cancer. The disease has been the subject of intensive research at both the basic scientific and clinical levels, becoming a paradigm for how to understand and treat oncogene-driven carcinomas. Although patients with EGFR-mutant tumours have increased sensitivity to tyrosine kinase inhibitors (TKIs), primary and acquired resistance to these ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
812
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 966 publications
(826 citation statements)
references
References 173 publications
(202 reference statements)
9
812
0
5
Order By: Relevance
“…179 Approximately 10-25% of EGFR-mutant lung adenocarcinomas do not respond to an EGFR TKI. 15 In addition to the previously mentioned mutations, even rarer primary mutations, such as D761Y, G719C, and E709A mutations, have also been shown to be insensitive to EGFR TKIs, and even more so when co-occurring with other genetic alterations. 196 Primary TKI resistance may also be mediated by the presence of other genetic alterations that affect signaling downstream from EGFR, such as mutation of KRAS, PIK3CA, and loss of PTEN expression.…”
Section: Primary Resistance To Egfr Targeted Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…179 Approximately 10-25% of EGFR-mutant lung adenocarcinomas do not respond to an EGFR TKI. 15 In addition to the previously mentioned mutations, even rarer primary mutations, such as D761Y, G719C, and E709A mutations, have also been shown to be insensitive to EGFR TKIs, and even more so when co-occurring with other genetic alterations. 196 Primary TKI resistance may also be mediated by the presence of other genetic alterations that affect signaling downstream from EGFR, such as mutation of KRAS, PIK3CA, and loss of PTEN expression.…”
Section: Primary Resistance To Egfr Targeted Therapymentioning
confidence: 99%
“…The exon 20 insertions frequently associated with EGFR-TKI non-responsiveness, including D770-N771insNPG, D770-N771insSVQ, D770-N771insG, and point mutations, including T790M, V769L, and N771T. 15,67 The most important mutation in exon 20 is T790M, which is associated with a small fraction of adenocarcinomas with primary resistance to EGFR TKI and over one-half of the patients with acquired resistance to EGFR TKI ( Figure 2). 12,[67][68][69][70][71] A comprehensive literature review by Yamamoto et al 33 indicated that 569 mutations were found in 2880 lung cancer patients (20%).…”
Section: Egfr Mutationsmentioning
confidence: 99%
See 3 more Smart Citations